Reporting of incorrect cause-of-death causal sequence on death certificates in the USA: using hypertension and diabetes as an educational illustration. Issue 1046 (18th September 2012) - Cheng, Tain-Junn; Lin, Ching-Yih; Lu, Tsung-Hsueh; Kawachi, Ichiro
Abstract : Background: Little is known about the extent of reporting an incorrect cause-of-death (COD) causal sequence on death certificates. Objective: To determine the frequency of incorrect reporting of hypertension as cause of diabetes on death certificates in the USA. Methods: Multiple-cause mortality files were used to identify death certificates which mentioned both hypertension and diabetes in the USA from 1985 to 2005. The frequency of reporting hypertension on the line below diabetes in part I of the death certificate was calculated. Results: The percentage of cases in which both hypertension and diabetes were included in part I of the death certificate, in which hypertension was reported on the line below diabetes on the death certificate—that is, suggesting that hypertension was a cause of diabetes—increased from 15.5% in 1985 to 36.1% in 2000 and 38.2% in 2005. Conclusions: The frequency of reporting of an incorrect COD causal sequence on death certificates in the USA has increased. Education, training and questioning the opinions of certifying physicians are needed to improve the quality of reporting of COD statements.